Complete mesocolic excision in colorectal cancer: a systematic review. (January 2015) - Kontovounisios, C.; Kinross, J.; Tan, E.; Brown, G.; Rasheed, S.; Tekkis, P.
Abstract Aim Several studies have suggested an increased lymph node yield, reduced locoregional recurrence and increased disease‐free survival after complete mesocolic excision (CME) for colorectal cancer. This review was undertaken to assess the use of CME for colon cancer by evaluating the technique and its clinical outcome. Method A literature search of publications was performed using PubMed and Medline. Only studies published in English were included. Studies assessed for quality and data were extracted by two independent reviewers. End‐points included number of lymph nodes per patient, quality of the plane of mesocolic excision, postoperative mortality and morbidity, 5‐year locoregional recurrence and 5‐year cancer‐specific survival. Results There were 34 articles comprising 12 retrospective studies, nine prospective studies and 13 original articles including case series, observational studies and editorials. Of the prospective studies, four reported an increased lymph node harvest and a survival benefit. The others reported an improvement in the quality of the specimen as assessed by histopathological examination. Laparoscopic CME has the same oncological outcome as open surgery but completeness of excision during laparoscopy may be compromised for tumours in the transverse colon. Conclusion Studies demonstrate that CME removes significantly more tissue around the tumour including maximal lymph node clearance. There is little information on serious adverse events after CME and a long‐term survival benefit has not been proved.